Sex-specific Differences in Myocardial Infarction – Literature Review - Janik, Natalia; Lenart, Julia; Wadowska, Zuzanna; Janowiak, Julia; Sobiś, Martyna; Górowska, Anna; Bogacka, Anna; Kiersznowska, Nina; Buchman, Małgorzata; Miłek, Barbara (Quality in Sport, 2026)
Background: Acute coronary syndromes in the course of ischemic heart disease remain the dominant cause of death in both female and male populations. In recent years, there has been increasing interest in gender-based differences in disease symptoms and outcomes. Taking the data into consideration and implementing it in a day to day practice might prove beneficial to patients and reduce the sex-specific disparities. Aim: The aim of this study is to gather recent information on the topic of sex-based differences in myocardial infarction and ischemic heart disease. We wanted to bring awareness to the issue and help clinicians understand what approach is best for patients prognosis. Material and methods: A review of studies including meta-analyses, clinical trials, cohort studies and systematic reviews was done with the use of various databases. The review focused on studies from last 10 years with individual older papers all mentioning the variations in women and men concerning ischemic heart disease and myocardial infarction. Results: Larger studies with better female representation seem to highlight the problem of women frequently carrying the burden of different risk profile, pathophysiology behind the disease, delayed presentation and less promising outcomes. However some studies in opposition show less significant differences in men and women regarding symptoms and mortality in myocardial infarction. Conclusions: The problem of sex differences in acute coronary syndromes should not be disregarded nor treated lightly since it has impact on both female morbidity and mortality. Part of research might still be inconclusive but that should only encourage researchers to delve deeper into it. Women seem to benefit from more personalized approach in both diagnostic procedures as well as treatment options.